Unsteady Effects of Shock Wave Induced Separation - Doerffer, Piotr; Hirsch, Charles; Dussauge, Jean-Paul.; Babinsky, Holger; Barakos, George N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume contains description of experimental and numerical results obtained in the UFAST project. The goal of the project was to generate experiment data bank providing unsteady characteristics of the shock boundary layer interaction. This new data bank should be useful for better understanding of the physical phenomena involved. The experiments concerned basic reference cases and the cases with application of flow control devices. The devices were freely chosen by research groups, depending on their experience. Obtained new data bank was used for the comparison with available simulation techniques, starting from RANS, through URANS and LES. Significant effort was also concentrated on hybrid RANS-LES methods.
Part I Transonic interactions -- Part II Nozzle flows -- Part III Shock reflection -- Part IV Summary by Work Packages.-.
Keywords: Engineering; Vibration; Engineering; Vibration, Dynamical Systems, Control; Classical Continuum Physics